Analisis evaluasi kinerja pendampingan Rumah BUMN Majene pada usaha mikro mahasiswa - Dela Safira; Herlina Ilyas; Muhammad Yusran (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2025)
This study aims to evaluate the performance of Rumah BUMN Majene mentoring for student micro-enterprises. Mentoring is considered necessary in supporting the development of entrepreneurial skills and increasing the capacity of student businesses. This study uses a descriptive qualitative approach. The results of the study indicate that the mentoring program is effective and has a positive impact, both in terms of packaging design, business legality, digital marketing, and financial management. The success of the program is supported by the active involvement of Rumah BUMN staff, collaboration with universities, and the implementation of training and coworking spaces. The evaluation was conducted using the CIPP (Context, Input, Process, Product) model, which indicates that this program has been aligned with the needs of business stakeholders. However, improvements are needed in legal assistance and financial management training so that the program can run more optimally. Public interest statements This statement affirms the commitment to supporting micro-student entrepreneurs through the Rumah BUMN Majene program. It aims to enhance skills, access, and knowledge among young entrepreneurs, thereby contributing to sustainable economic growth at both local and national levels. Through collaboration among various institutions, this program has the potential to serve as a successful model for community empowerment and economic strengthening.